Mathematical modeling ability based on students' cognitive style in linear program material - Windya, Pelangi Mutia; Noer, Sri Hastuti (Desimal: Jurnal Matematika, 2023)
Modeling abilities and student characteristics are very important in learning mathematics at school. One of the characteristics that must be considered is cognitive style. This study aims to describe the mathematical modeling abilities of students with field independent (FI) and field dependent (FD) cognitive styles in linear programming material. The design of this research is descriptive-qualitative. This study analyzed the mathematical modeling abilities, and then, using a purposive sampling technique, 4 subjects were selected as samples, 2 each for field independent (FI) and field dependent (FD) cognitive style subjects. Data on students' mathematical modeling abilities were obtained through task-based interviews and written tests, while cognitive style data were obtained through the Group Embedded Figure Test (GEFT) written test. The validity of the data was then tested using time triangulation and then analyzed through the stages of data reduction, presentation, and drawing conclusions. So, the results of this study indicate that in modeling problems, students who have a cognitive style of FI tend to be able to fulfill indicators of understanding actual problems, preparing mathematical models from real models, and interpreting mathematical results in real situations. whereas students who have a cognitive style like FD tend to only be able to understand the real problem.